Targeted chitosan nanobubbles as a strategy to down-regulate microRNA-17 into B-cell lymphoma models - Capolla, Sara; Argenziano, Monica; Bozzer, Sara; D’Agaro, Tiziana; Bittolo, Tamara; De Leo, Luigina; Not, Tarcisio; Busato, Davide; Dal Bo, Michele; Toffoli, Giuseppe; Cavalli, Roberta; Gattei, Valter; et al. (Frontiers in Immunology, 2023)
Introduction MicroRNAs represent interesting targets for new therapies because their altered expression influences tumor development and progression. miR-17 is a prototype of onco-miRNA, known to be overexpressed in B-cell non-Hodgkin lymphoma (B-NHL) with peculiar clinic-biological features. AntagomiR molecules have been largely studied to repress the regulatory functions of up-regulated onco-miRNAs, but their clinical use is mainly limited by their rapid degradation, kidney elimination and poor cellular uptake when injected as naked oligonucleotides. Methods To overcome these problems, we exploited CD20 targeted chitosan nanobubbles (NBs) for a preferential and safe delivery of antagomiR17 to B-NHL cells. Results Positively charged 400 nm-sized nanobubbles (NBs) represent a stable and effective nanoplatform for antagomiR encapsulation and specific release into B-NHL cells. NBs rapidly accumulated in tumor microenvironment, but only those conjugated with a targeting system (antiCD20 antibodies) were internalized into B-NHL cells, releasing antagomiR17 in the cytoplasm, both in vitro and in vivo. The result is the down-regulation of miR-17 level and the reduction in tumor burden in a human-mouse B-NHL model, without any documented side effects. Discussion Anti-CD20 targeted NBs investigated in this study showed physico-chemical and stability properties suitable for antagomiR17 delivery in vivo and represent a useful nanoplatform to address B-cell malignancies or other cancers through the modification of their surface with specific targeting antibodies.